2020
DOI: 10.1159/000509286
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Treatments for Waldenström Macroglobulinemia

Abstract: Waldenström macroglobulinemia (WM) is a rare lymphoplasmacytic lymphoma. The primary goal of therapy is to reduce symptoms related to direct infiltration of the bone marrow and decrease monoclonal IgM-associated complications. Active agents in the management of WM can be broadly classified as rituximab-alkylator combination therapy, proteasome inhibitor-based therapy, and Bruton’s tyrosine kinase inhibitor-based therapy. <i>MYD88</i><sup>L265P</sup> and <i>CXCR4</i> genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Of the many BTK inhibitors developed in the last 10 years, three (ibrutinib/PCI-32765, acalabrutinib/ACP 196, and zanubrutinib/BGB 3111) are now used in the clinic to treat B cell malignancies ( Figure 2 a and Table 2 ). Ibrutinib and acalabrutinib are authorized for untreated and R/R CLL/SLL and CLL with 17p deletion [ 146 , 147 , 148 , 149 ], ibrutinib and zanubrutinib are authorized for R/R MZL patients who have received at least one line of an anti-CD20-based regimen [ 149 ], and ibrutinib, acalabrutinib and zanubrutinib are authorized for WM patients and for MCL patients who have received at least one line of treatment [ 119 , 147 , 148 , 149 , 150 ]. These three agents are orally administered alone or in combination with an anti-CD20 mAb such as rituximab ( Table 2 ).…”
Section: Current Treatments and Clinical Trials Of B Cell Malignancie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the many BTK inhibitors developed in the last 10 years, three (ibrutinib/PCI-32765, acalabrutinib/ACP 196, and zanubrutinib/BGB 3111) are now used in the clinic to treat B cell malignancies ( Figure 2 a and Table 2 ). Ibrutinib and acalabrutinib are authorized for untreated and R/R CLL/SLL and CLL with 17p deletion [ 146 , 147 , 148 , 149 ], ibrutinib and zanubrutinib are authorized for R/R MZL patients who have received at least one line of an anti-CD20-based regimen [ 149 ], and ibrutinib, acalabrutinib and zanubrutinib are authorized for WM patients and for MCL patients who have received at least one line of treatment [ 119 , 147 , 148 , 149 , 150 ]. These three agents are orally administered alone or in combination with an anti-CD20 mAb such as rituximab ( Table 2 ).…”
Section: Current Treatments and Clinical Trials Of B Cell Malignancie...mentioning
confidence: 99%
“…A phase III trial (NCT02004522) of duvelisib vs. ofatumumab (an anti-CD20) in patients with R/R CLL/SLL was terminated in 2021 after the occurrence of serious adverse events, including severe infections and diarrhea/colitis [ 161 ]. Clinical evaluations of the efficacy of idelalisib as a monotherapy and of duvelisib combined with anti-CD20 (obinutuzumab) in R/R MM were recently reviewed by Grimont et al [ 119 ]. Idelalisib is associated with significant hepatotoxicity, which may limit the drug’s use in WM [ 118 ].…”
Section: Current Treatments and Clinical Trials Of B Cell Malignancie...mentioning
confidence: 99%
“…Ibrutinib has been approved to treat B cell cancers like mantle cell lymphoma, 2 chronic lymphocytic leukemia, 3 marginal zone lymphoma, and Waldenström's macroglobulinemia, as well as chronic graft-versus-host disease. 4 More recently, BTK inhibitors, including ibrutinib, as well as other known drugs, were screened for potential activity against COVID-19. 5,6 Preclinical and clinical studies have shown that ibrutinib is susceptible to rapid and extensive phase I oxidative metabolism mediated by cytochrome P450 3A.…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib is a once‐daily small molecule inhibitor that binds irreversibly to Bruton's tyrosine kinase (BTK) 1 via its covalent acrylamide warhead, which blocks malignant B cell receptor signaling, disrupts B cell adhesion and migration, and drives malignant B cells into apoptosis. Ibrutinib has been approved to treat B cell cancers like mantle cell lymphoma, 2 chronic lymphocytic leukemia, 3 marginal zone lymphoma, and Waldenström's macroglobulinemia, as well as chronic graft‐versus‐host disease 4 . More recently, BTK inhibitors, including ibrutinib, as well as other known drugs, were screened for potential activity against COVID‐19 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Targeting BTK in CLL and MCL with ibrutinib results in direct inhibition of cell proliferation and homing/migration due to disruption of BCR and chemokine receptor signaling (Herman et al, 2011;de Rooij et al, 2012;Ponader et al, 2012;Hendriks et al, 2014;Pal Singh et al, 2018). Based on the clinical evidence, ibrutinib has been given the United States Food and Drug Administration (FDA) approval for the treatment of multiple B cell malignances, including CLL/small lymphocytic lymphoma (SLL), MCL, marginal zone lymphoma (MZL) and Waldenstrom macroglobulinemia (WM) (Hendriks et al, 2014;Pal Singh et al, 2018;Zi et al, 2019;Bond and Maddocks, 2020;Castillo et al, 2020b;Grimont et al, 2020;Hanna et al, 2020;Noy et al, 2020;Treon et al, 2021). Furthermore, ibrutinib, as monotherapy or in combination therapies with other targeted drugs (such as anti-CD20, anti-PD-1/PD-L1 and inhibitors of Bcl-2, PI-3Kδ or proteosome), has demonstrated efficacy in patients with diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), Richter's transformation (RT), multiple myeloma (MM), B cell pro-lymphocytic leukemia (B-PLL), acute lymphoblastic leukemia (ALL), lymphoproliferative disorders (LPD), and primary and secondary central nervous system lymphomas (PCNSL/SCNSL) in recent clinical trials (Hendriks et al, 2014;Pal Singh et al, 2018;Chari et al, 2020;Chen et al, 2020;Fowler et al, 2020;Oka et al, 2020;Schaffer et al, 2020;Graf et al, 2021;Hodkinson et al, 2021;Lewis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%